The Effectiveness of Akm (Minimum Competency Assessment) Practice on Student’s English Learning Outcomes at SMA Negeri 11 Samarinda - Elva Nadia Zulkarnain; Godefridus Bali Geroda; Widi Syahtia Pane (Inquest Journal, 2023)
In the learning process at school, of course, teachers and students have learning targets or minimum scores of success indexes that students must achieve. In that case, students' understanding and effective test tools in achieving learning outcomes are very necessary. The research was conducted by taking samples in the tenth grade at SMA Negeri 11 Samarinda, this study aims to see whether there is real significance if students are given different types and forms of tests in creating better learning outcomes. How important is the comfort and understanding of students in answering and understanding exercises or exams related to learning material. Therefore, researcher used AKM to try whether there is a significance in the ability to understand questions and increase learning outcomes. In the end, the results of the research show that AKM is effective for student learning outcomes. and is very good for measuring students' understanding abilities in learning material, especially English lesson.